Forschen für den Justizvollzug: Am Anfang steht ein visionäres Engagement für den Theorie-Praxis-Transfe - Cotti, Patrick; Urwyler, Christopher; Mandach, Laura, von (Über Mauern blicken - 25 Jahre Forschen im Justizvollzug: Festschrift für Ueli Hostettler zum 65. Geburtstag, 2025)
The article highlights the role of the Prison Research Group, led by Ueli Hostettler, which has established itself over many years as a driving force for the sustainable development of the penal and correctional system. Using key research projects—such as those on education in the prison system, the working conditions of prison staff, and the development of the “Prison Barometer”—it shows how practical research contributes to quality development. (machine translation)